1992
DOI: 10.1007/bf02245297
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of carbamazepine, phenytoin, diazepam and clonazepam on inhibitory avoidance learning in mice

Abstract: Four antiepileptic drugs were investigated in an inhibitory avoidance task in mice. Following IP administration 30 min prior to training, carbamazepine (32 mg/kg), phenytoin (30-60 mg/kg), diazepam (2-8 mg/kg) and clonazepam (0.125-0.5 mg/kg) impaired retention. When administered 30 min prior to the retention test none of the drugs under investigation affected retention. The drugs did not affect latencies in the hot plate test. This indicates that in the case of pretraining drug administration effects on reten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…The drug doses were calculated from the salt form and based on doses used previously [4,[24][25][26]. Commercially available PHEN solution (Hidantal; Sanofi-Aventis, Suzano, SP, Brazil) was diluted in distilled water and administered intraperitoneally (i.p.)…”
Section: Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…The drug doses were calculated from the salt form and based on doses used previously [4,[24][25][26]. Commercially available PHEN solution (Hidantal; Sanofi-Aventis, Suzano, SP, Brazil) was diluted in distilled water and administered intraperitoneally (i.p.)…”
Section: Drugsmentioning
confidence: 99%
“…All of the drugs and their vehicles were administered in a constant volume of 10 ml/kg. The drug doses were calculated from the salt form and based on doses used previously [4,[24][25][26]. The dose of veratrine (dissolved in saline; Sigma-Aldrich) was based on a pilot study that showed that 0.4 mg/kg did not alter hyperlocomotion induced by MPH.…”
Section: Drugsmentioning
confidence: 99%
“…Esses dados assemelham-se a estudos que investigaram os efeitos de benzodiazepínicos na esquiva inibitória em camundongos, em que foi relatado que a administração de benzodiazepínicos prejudicou a tarefa de esquiva inibitória com o animal, exibindo significativamente menos tempo para entrar no compartimento no qual sua resposta foi punida (Nabeshima, Tohyama, Ichihara, & Kameyama, 1990;Voigt & Morgenstern, 1992).…”
Section: Discussionunclassified